Phosphoric Acid-Activated Rice Husk Biochar for Enhanced Cadmium Adsorption - Panara, Viral; Panchal, Vikas; Travadi, Satayu; Bhatt, Harmish (International Journal of Aquatic Research and Environmental Studies, 2026)
In farming areas, the amount of rice husks piled up is difficult to clean up and water filled with heavy metals can make the food unfit to be consumed. In this study, the effectiveness of phosphoric acid to activate rice husk biochar was improved, which makes it more efficient in removing Cd ions from wastewater. The raw rice husk was weighed and mixed with H3PO4 in 1:1 ratio and heated at 550 degrees Celsius.The process is called pyrolysis. Using phosphoric acid treatment, the surface area went up from 64.2 to 268.4 m²/g, and it also successfully added phosphorus groups to the surface. The adsorption process was investigated by performing batch adsorption experiments for various initial concentrations, pH and contact times. The highest level of Cd²+ that was absorbed was 42.51 mg per gram at pH 6.0, which is 8 times as much as the absorption of the unmodified biochar of 5.12 mg per gram. The reaction rate is very well described by the pseudo-second-order model (R2 = 0.998), suggesting that chemisorption is the major process occurring during the reaction. Better correlation was obtained when the equilibrium data were plotted on the Langmuir isotherm (R² = 0.996), indicating that the adsorption occurred in a single layer on sites that were distributed uniformly. This process converts low-value farm waste into a solid that can absorb and so provides a means of utilizing resources and ensuring farm systems are safe.
Keywords: Rice husk biochar, chemical activation, cadmium adsorption, agricultural waste valorization, wastewater remediation.